KLASIFIKASI JENIS IKAN FAMILIA CYPRINIDAE DI SUNGAI PANGI DESA PENGGUMBUK KECAMATAN RANTAU BAYUR KABUPATEN BANYUASIN PROVINSI SUMATERA SELATAN (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2016)
Research of  clasification    of   fish cyprinidae  Family    at  Pangi  river   Pengumbuk  village,  Banyuasin   regency  Sumatera Selatan province on  Agustus-September  2013. This research  utilited  the direct   observation  method  by collecting fish samples which were caught by fisherman along Pengumbuk river.  The result of the research geted 8  genera and 9 species.Key words : pengumbuk river, Classification,  Cyprinidae, spesies.